PENGARUH MODEL MIND MAPPING TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM PKn KELAS V SD - Saputra, Adi; Utami, Sri; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The problem in this research is "What is the influence of applying Mind Mapping model to student learning outcomes in civic education learning in class V State Elementary School 36 Pontianak South?". This research uses experimental method of quasi-experimental type with experimental design of Non-Equivalent Control Group Design. The population of all students in grade V of Pontianak South. Sampling is non probability sampling type purposive sampling is student in class V State Elementary School 36 Pontianak South. Technique of data collection using measurement technique form using objektive test. The result of data processing is obtained by mean of pre-test of control class 58,44 and mean experiment class pre-test 57,9. Based on the data normality test results using the formula of chi-squares data is normally distributed. Futhermore, the homogenneity test data with Fcount(1,12)< Ftable (1,98), expressed homogeneous and continued t test by formula polled varians, obtained t_ count (4,26) > t _table (1,6749) with dk = 48, then Ha accepted. So, it can be concluded there is influence of student learning outcomes that apply Mind Mapping model. The result of calculation effect size (ES), obtained by 0.57 (medium criterion). This means that the application of a contextual approach to civic education learning provides a moderate impact on the outcomes of fourth grade students of State Elementary School 36 Pontianak South.Â Keyword : Influence, Mind Mapping, Learning outcomesÂ